THE USE OF AUTHENTIC MATERIALS IN IMPROVING STUDENTS’ READING INTEREST - Nurul Aryanti; Aria Septi Anggaira (The Journal of English Literacy Education: The Teaching and Learning of English as a Foreign Language, 2016)
THE USE OF AUTHENTIC MATERIALS IN IMPROVING STUDENTS’ READING INTEREST Nurul Aryanti Politeknik Negeri Sriwijaya, Palembang, South Sumatera nurulpoltek@yahoo.com Aria Septi Anggaira ariasepti@yahoo.com Abstract: This study is aimed at finding out the impacts of the use of authentic materials in improving the reading interest of VIIIC students of SMPN 4 Metro in the academic year of 2015/2016. The data were collected by doing observation during the English teaching and learning process in the classroom, giving a questionnaire to the students, and selecting the authentic texts based on certain criteria. The data of the students’ reading interest were analysed using quantitative and qualitative techniques. The findings reveal three important results. First, there are three kinds of materials that fulfill the criteria of authenticity. They are an advertisement, announcement, and descriptive  text in the form of an article taken from a High End Teen magazine. Second, there are four types of students’ positive attitudes towards the implementation of authentic materials. Those are the students’ willingness to own the materials, the students’ willingness to use the authentic materials in the next meetings, the students’ preferences to use the original form of authentic materials instead of the copied materials, and the students’ willingness to comment about the topics and the pictures of the authentic materials. Third, there are quantitative and qualitative data related to the improvement of the students’ reading interest. The two kinds of data show that there are some significant improvements of the students’ reading interest after the authentic materials are used in the classroom. Key words: reading, authentic, material, interest.